Perbandingan Analisis Prediksi Kebangkrutan Menggunakan Model Altman Pertama, Altman Revisi, dan Altman Modifikasi dengan Ukuran dan Umur Perusahaan sebagai Variabel Penjelas (Studi Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia) - Ayu Suci Ramadhani; Niki Lukviarman (Jurnal Siasat Bisnis, 2009)
This study observes the bankruptcy prediction models introduced by Altman; the First Altman model, the Revised Altman model, and the Modified Altman model to predict bankruptcy for manufacturing companies listed in the Indonesian Stock Exchange. The research was conducted for forty-two manufacturing companies that matched criteria in the selection of the sample over the years 2004-2007 based on published data for the same period. To accommodate various Almant models, the data was then calculated based on financial ratio and the data have been processed further to find the bancruptcy index as suggested by the models. The results of the three models are then compared with the use of company’s age and size as descriptive information to predict the company’s bankruptcy potential. The result of comparative data in bankruptcy prediction is that; the first Altman provides the highest percentage in predicting the bankruptcy. The research also found that the company categorized under small groups and under the age of 30 were likely to go bankcrupt in compare to the other groups. Keywords:    financial distress, bankruptcy Index, bankruptcy prediction model, size of the company, age of the company.